2016
DOI: 10.3389/fnint.2016.00033
|View full text |Cite
|
Sign up to set email alerts
|

Benefits from Vergence Rehabilitation: Evidence for Improvement of Reading Saccades and Fixations

Abstract: We hypothesize that binocular coordination of saccades is based on continuous neuroplasticity involving interactions of saccades and vergence. To test this hypothesis we study reading saccades in young students who were diagnosed for vergence disorders before and after vergence rehabilitation. Following orthoptic evaluation and symptomatology screening, 5 weekly sessions of vergence rehabilitation were applied with the REMOBI vergence double step protocole (see Kapoula et al., 2016). Using the Eyeseecam videoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 39 publications
1
13
0
Order By: Relevance
“…Another important aspect is the weakening of the correlation between intra-saccadic disconjugacy and the disconjugacy during the following fixation. Previous studies showed significant correlation between these two parameters 38,61 ; such correlation was associated with a better capacity for reducing the disparity during fixation that results from the intra-saccadic disconjugacy. In the present study, the prisms altered this correlation that became weaker than in the lenses and in the control condition, and this for the interference Stroop task (see Fig.…”
Section: Discussionmentioning
confidence: 86%
“…Another important aspect is the weakening of the correlation between intra-saccadic disconjugacy and the disconjugacy during the following fixation. Previous studies showed significant correlation between these two parameters 38,61 ; such correlation was associated with a better capacity for reducing the disparity during fixation that results from the intra-saccadic disconjugacy. In the present study, the prisms altered this correlation that became weaker than in the lenses and in the control condition, and this for the interference Stroop task (see Fig.…”
Section: Discussionmentioning
confidence: 86%
“…This is an exciting area of research: though orthoptic training has been considered the standard of care rehabilitation for the dyslexic population, perhaps there are new avenues to design rehabilitation programs to train dyslexic adolescent eye movements to respond more quickly and accurately to these audiovisual stimuli. There have been some small preliminary studies that have already demonstrated improvement in reading (decreased regressive saccades, decreased fixation duration) in other populations 28 , 64 . In addition to the work that is currently being conducted, we would encourage more research in this exciting avenue specifically in the dyslexic population 65 .…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, perhaps these preliminary results related to eye movement deficits could be useful in planning retraining exercises. Previous studies using a double step vergence paradigm on the REMOBI machine have shown lasting improvements in reading saccades, fixations, and vergence measurements 19,28,[62][63][64] . Future research should repeat these experiments to verify audiovisual vergence retraining as a viable new rehabilitation technique.…”
Section: Correlation Between Vergence and Saccade Abnormalities To Smentioning
confidence: 91%
See 1 more Smart Citation
“…Also, it seems worth researching whether monocular occlusion technique (as suggested by Stein and Fowler 67 ) or vergence training (orthoptic or optometric visual therapy), commonly used in case of heterophoria and/or other vergence anomalies, 68,69 may significantly improve fixation and motor control in dyslexia. The positive effect of vergence rehabilitation on saccades and fixation during reading was recently examined by Daniel et al, 70 but further studies in that area are necessary.…”
Section: Limitation Of the Study And Future Directionmentioning
confidence: 98%